Assessing the association of sustainable agriculture with rural household food security (considering ecological, economic, and social aspects) - Sahraei, Salman; Pakravan-Charvadeh, Mohammad Reza; Gholamrezai, Saeed; Rahimian, Mehdi (Frontiers in Nutrition, 2022)
Due to the importance of sustainability in the world, we follow the missing pieces of the puzzle of sustainable agriculture and food security as a huge gap in the literature. To achieve this goal, a survey was analyzed to assess the linkage between these two concepts in the rural areas in Lorestan province in Iran. The status of food security was assessed using US Household Food Security Survey Module (HFSSM). A standard questionnaire extracted from the related literature was applied to calculate sustainability indicators. The results showed that the status of food security among households with no children (70%) was better than those with one or more children (28%). According to the Tobit model, none of the sustainability dimensions had a significant association with food insecurity. The results support the fact that the assessment of agricultural sustainability at the microeconomic level, short-term period, and a small, specified location cannot lead to reliable results due to the similar behaviors of farmers in these areas. The low level of agricultural sustainability is due to the lack of macroeconomic policies in the region to promote and disseminate the principles of sustainability, lack of plans and actions to promote sustainability by stakeholders and policymakers, ignorance of the target community, as subsistence producers who fall into a deprivation trap. The results suggest that policymakers should use two short-term and long-term strategies to improve the level of agricultural sustainability and increase food security status.